2001
DOI: 10.1074/jbc.m008662200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Interleukins IL-1α, IL-1β, IL-4, IL-6, and IL-7 Show Different and Specific Calcium-independent Carbohydrate-binding Properties

Abstract: A method was developed for the determination of putative lectin activities of cytokines. It involved the immunoblotting measurement of the quantity of these cytokines unbound to a series of different immobilized glycoconjugates and displacement of the bound cytokines with oligosaccharides of known structures. This method allows demonstrating that the following interleukins specifically recognize different oligosaccharide structures in a calcium-independent mechanism: interleukin-1␣ binds to the biantennary dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 53 publications
0
50
0
Order By: Relevance
“…The IL-1␤ was chosen because its receptor is not sialylated glycoprotein 68 and it can interact with the cell membrane GM4 sialylated glycolipid, Neu5Aca2-3Gal␤1-ceramide. 69 Thus, the detection of any diminution of the proliferative effects of IL-1␤ in cultures pretreated with C. perfringens Nase would indicate some collateral action of this enzyme (eg, through desialylation of cell membrane gangliosides) that might indirectly modify cellular proliferation. Then, we compared the magnitude of the proliferative effects of the same doses of PDGF-BB and IGF-2 in 3-day-old subconfluent cultures of normal human skin fibroblasts and Neu1-deficient fibroblasts derived from patients with congenital sialidosis.…”
Section: Assessments Of Cellular Proliferationmentioning
confidence: 99%
“…The IL-1␤ was chosen because its receptor is not sialylated glycoprotein 68 and it can interact with the cell membrane GM4 sialylated glycolipid, Neu5Aca2-3Gal␤1-ceramide. 69 Thus, the detection of any diminution of the proliferative effects of IL-1␤ in cultures pretreated with C. perfringens Nase would indicate some collateral action of this enzyme (eg, through desialylation of cell membrane gangliosides) that might indirectly modify cellular proliferation. Then, we compared the magnitude of the proliferative effects of the same doses of PDGF-BB and IGF-2 in 3-day-old subconfluent cultures of normal human skin fibroblasts and Neu1-deficient fibroblasts derived from patients with congenital sialidosis.…”
Section: Assessments Of Cellular Proliferationmentioning
confidence: 99%
“…There, it functions as first line of defense against airway infection and plays a major role in mucociliar clearance of the airways. Pathogens, particles and other chemicals are caught up in a mucus layer covering beating cilia, which constantly sweep the mucus from distal to proximal airways to finally force it out of the lung [22][23][24]. This mucus layer is composed of a low-viscosity and therefore low resistance liquid layer up to the height of the cilia supporting the cilia beating and an overlying high-viscosity gel layer [23,25,26].…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%
“…These data did not take into account the possibility that IL-6 could be, as other interleukins (17), a bi-functional molecule having, beside a receptor-binding domain, a carbohydrate recognition domain (CRD). As demonstrated for interleukin 2 (IL-2; Ref.…”
mentioning
confidence: 99%
“…Recent studies (17) demonstrated that IL-6 specifically binds to nervous tissue glycoproteins bearing the HNK-1 epitope (glucuronic acid 3-sulfate), the structure having been determined (23,24). The HNK-1 epitope is an onco-fetal antigen (25)(26)(27)(28)(29)(30), especially concentrated at early stages of development on glycoproteins considered as "cell-adhesion molecules": the N-CAM (31,32), the J1 glycoprotein (33), the myelin-associated glycoprotein (MAG; 4,34,35,36), the P0 myelin glycoprotein (6,37,38), the myelin-oligodendrocyte glycoprotein (MOG; Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation